The application of 1H high-resolution magic-angle spinning NMR for the study of clay-organic associations in natural and synthetic complexes - Simpson, André J (Langmuir : the ACS journal of surfaces and colloids, 2006)
The preferential sorption of model compounds to calcium-exchanged montmorillonite surfaces was investigated using 1H high-resolution magic-angle spinning (HR-MAS) and liquid-state NMR. Synthetic mixtures, representing the major structural categories abundant in natural organic matter (NOM), and two soil extracts were sorbed to montmorillonite. The NMR spectra indicate that, of the organic components observable by 1H HR-MAS NMR, aliphatic components preferentially sorb to the clay surface, while carbohydrates and amino acids mainly remain in the supernatant. These results may help explain the highly aliphatic nature of organic matter associated with clay fractions in natural soils and sediments. Investigations using the synthetic mixtures demonstrate a specific interaction between the clay surface and the polar region in 1-palmitoyl-3-stearoyl-rac-glycerol. Similar observations were obtained with natural soil extracts. The results presented have important implications for understanding the role of organoclay complexes in natural processes, and provides preliminary evidence that HR-MAS NMR is a powerful analytical technique for the investigation of organoclay complex structure and conformation